Methodology and Demographics of a Brief Adolescent Alcohol Screen Validation Study. Issue 11 (November 2019) - Bromberg, Julie R.; Spirito, Anthony; Chun, Thomas; Mello, Michael J.; Casper, T. Charles; Ahmad, Fahd; Bajaj, Lalit; Brown, Kathleen M.; Chernick, Lauren S.; Cohen, Daniel M.; Fein, Joel; Horeczko, Tim; et al.
Abstract : Objective: The aim of this study was to determine the psychometric properties of the National Institute on Alcohol Abuse and Alcoholism (NIAAA) 2-question alcohol screen within 16 Pediatric Emergency Care Applied Research Network pediatric emergency departments. This article describes the study methodology, sample characteristics, and baseline outcomes of the NIAAA 2-question screen. Methods: Participants included 12- to 17-year-olds treated in one of the participating pediatric emergency departments across the United States. After enrollment, a criterion assessment battery including the NIAAA 2-question screen and other measures of alcohol, drug use, and risk behavior was self-administered by participants on a tablet computer. Two subsamples were derived from the sample. The first subsample was readministered the NIAAA 2-question screen 1 week after their initial visit to assess test-retest reliability. The second subsample is being reassessed at 12 and 24 months to examine predictive validity of the NIAAA 2-question screen. Results: There were 4834 participants enrolled into the study who completed baseline assessments. Participants were equally distributed across sex and age. Forty-six percent of the participants identified as white, and 26% identified as black. Approximately one quarter identified as Hispanic. Using the NIAAA 2-question screen algorithm, approximately 8% were classified as low risk, 12% were classified as moderate risk, and 4% were classified as highest risk. Alcohol use was less likely to be reported by black participants, non-Hispanic participants, and those younger than 16 years. Discussion: This study successfully recruited a large, demographically diverse sample to establish rates of the NIAAA screen risk categories across age, sex, ethnicity, and race within pediatric emergency departments.